Analysis of the of Customer Orientation on MSMEs’ Performance: Testing the Mediating Role of Innovativeness - Athiyah, Farah; Darmawan, Baziedy Aditya (MEC-J (Management and Economics Journal), 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia make an important contribution to the national economy but face various challenges that can hinder the optimization of their business performance. Although previous research has shown that customer orientation and innovativeness can improve business performance, studies focusing on this topic in developing countries are still limited. Therefore, this study aims to analyze the effect of customer orientation on MSME's performance mediated by innovativeness in Sleman district and Yogyakarta City. 82 MSME respondents in Sleman Regency and Yogyakarta City completed a questionnaire and were analyzed using SmartPLS4 with a non-probability convenience sampling technique. The results showed that customer orientation does not positively influence MSME's performance. However, there is a positive relationship between customer orientation and innovativeness, where customer orientation encourages an increase in innovativeness. In addition, innovativeness has a significant positive influence on MSME's performance. However, innovativeness does not significantly mediate between customer orientation and MSMEs' performance. MSMEs players can use the results of this study to consider the effect of innovativeness on customer orientation and MSMEs' performance.